Energy Drinks Consumption, Knowledge, and Beliefs among Medical University Students in University of Zawia: A Cross-Sectional Study - Hana Alazraq; Shahrazad Gazeti; Salihah Mustafa; Mufida Khetresh; Reemah Almadah; Karima Elalagi (Khalij-Libya Journal of Dental and Medical Research, 2025)
Recently, energy drink consumption has become very common among teenagers and young adults. This study aimed to assess the frequency and usage pattern of energy drinks consumption among university students in Zawia, Libya, and their knowledge and beliefs about the effects of energy drinks. A cross-sectional survey of 180 students from three different medical colleges (medicine, dentistry, and pharmacy) at Zawia University was conducted, with data collection taking place through a self-administered questionnaire between October 2023 and January 2024. The majority of participants (52.2%) were aged 22–24 years, with females comprising 77.8% of the sample. Only about 12.2% consume them regularly, and 30.0% occasionally. About 72.7% of the students reported drinking one can of energy drink per day, with the most common reasons given by the respondents for using energy drinks being to enhance alertness, overcome apathy and lethargy, and approximately 10.0% used them to improve athletic performance before exercise. The major side effects experienced by this study were headaches (23.3%) and sleep disturbances (15.0%). College affiliation also showed a significant association, with medical students reporting the highest consumption, followed by students in dentistry and pharmacy. Exam periods were strongly associated with energy drink consumption of participants who consumed energy drinks during exams. The study reported that ED consumption among students at Zawia University was low, which might be due to gender differences. This study determined that consumption of EDs is relatively high among students at the medical college in comparison to dentistry and pharmacy colleges.